GIS research project on karst in Bulgaria - Jelev, Georgi; Stefanova, Dilyana; Stefanov, Petar; Bonev, Dimitar; Stoyanova, Alexandra; Chilakova, Dema (Annual of Natural Sciences Department, 2021)
This paper is focusing on the development of geographic information system (GIS) which aim is to facilitate the study of anthropogenic influence on karst systems in Bulgaria by analysing characteristic model areas. Five model areas are selected representing different types of karst systems in the context of the political, socio-economic, and global changes. This study is part of the project â€žCurrent impacts of global changes on evolution of karst (based on the i ntegrated monitoring of model karst geosystems in Bulgaria)â€, Science Research Fund.